Therapeutic Re-Activation of Protein Phosphatase 2A in Acute Myeloid Leukemia - Ramaswamy, Kavitha; Spitzer, Barbara; Kentsis, Alex (Frontiers in Oncology, 2015)
Protein phosphatase 2A (PP2A) is a serine/threonine phosphatase that is required for normal cell growth and development. PP2A is a potent tumor suppressor, which is inactivated in cancer cells as a result of genetic deletions and mutations. In myeloid leukemias, genes encoding PP2A subunits are generally intact. Instead, PP2A is functionally inhibited by post-translational modifications of its catalytic C subunit, and interactions with negative regulators by its regulatory B and scaffold A subunits. Here, we review the molecular mechanisms of genetic and functional inactivation of PP2A in human cancers, with a particular focus on human acute myeloid leukemias (AML). By analyzing expression of genes encoding PP2A subunits using transcriptome sequencing, we find that PP2A dysregulation in AML is characterized by silencing and overexpression of distinct A scaffold and B regulatory subunits, respectively. We review the mechanisms of functional PP2A activation by drugs such as fingolimod, forskolin, OP449, and perphenazine. This analysis yields two non-mutually exclusive mechanisms for therapeutic PP2A re-activation: i) allosteric activation of the phosphatase activity, and ii) stabilization of active holo-enzyme assembly and displacement of negative regulatory factors from A and B subunits. Future studies should allow the development of specific and potent pharmacologic activators of PP2A, and definition of susceptible disease subsets based on specific mechanisms of PP2A dysregulation.